A quasi-experimental study on plate colours on plate waste percentage among patients in a public hospital in Selangor, Malaysia - Omar, Noraida; Jamaludin, Rosita; Shalihin, Siti Amirah Shaheera (Malaysian Journal of Medicine and Health Sciences, 2024)
Introduction: The plate and the foods create visual platescapes that can influence food intake in many ways. However, whether the plate colour could indirectly enhance hospitalised patients' appetite and reduce plate waste is unclear. This study aimed to determine plate waste percentage and whether blue plate (BP) has a lower plate waste percentage than white plate (WP) when served to hospitalised patients. This study also determined the interaction effect between plate colours on socio-demographic characteristics, medical background, nutritional status and appetite level with plate waste percentage. Materials and methods: This quasi-experimental study was conducted among patients who received a normal diet during one lunch hour and those in a public hospital in Selangor who received a normal diet. Plate waste was evaluated for the lunch menu for 125 meals. All the patients were randomly chosen to receive hospital meals from a WP or BP on the same day during lunch hour, and patients, with assistance from the researcher, completed the questionnaire. The primary outcome was the total plate waste percentage between the patients receiving BP and those receiving WP. Results: The result shows only a significant interaction effect between the plate colour and education level. After controlling for all the covariates, the plate waste percentage between the WP and BP remains significant. Conclusion: A significant difference in plate waste percentage between the plate colours suggests that BP indirectly improve appetite and reduces plate waste among hospitalised patients.